2022
DOI: 10.18311/ti/2022/v29i3/29732
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and Assessment of Antidotal Effects of Diphenhydramine against Acute Carbaryl Insecticide Poisoning in a Chick Model

Abstract: Diphenhydramine antagonizes poisoning produced by cholinesterase (ChE) inhibiting insecticides. This study examines the effects of diphenhydramine against acute poisoning induced by the carbamate insecticide carbaryl in a chick model. The effects of diphenhydramine on the 24 h median Lethal Dose (LD50), and acute toxicity of carbaryl were assessed in chicks (7-15 days old). The plasma and whole brain ChE activities were measured electrometrically in vitro and in vivo. Diphenhydramine at 10mg/Kg Body wt. admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…However, other sources of heterogeneity could be the types of insecticides used, since they variably and differentially inhibit ChEs, and the species of experimental animals, since they inherently possess ChEs of various physiological activities in the blood or brain [43,44]. In support of our meta-analysis, which was conducted on blood and brain ChEs in vivo (mice, rats, and chicks), in vitro studies on human PChE and EChE [30] and chick PChE and BChE [21,22] suggested that diphenhydramine might partially protect the enzyme from additional inhibition induced by OP or CA insecticides. However, at the current stage, we cautiously draw such a conclusion, since the prediction of a future study by the drapery plot suggested the possibility of a shift of the point of effect size toward the diphenhydramine intervention.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…However, other sources of heterogeneity could be the types of insecticides used, since they variably and differentially inhibit ChEs, and the species of experimental animals, since they inherently possess ChEs of various physiological activities in the blood or brain [43,44]. In support of our meta-analysis, which was conducted on blood and brain ChEs in vivo (mice, rats, and chicks), in vitro studies on human PChE and EChE [30] and chick PChE and BChE [21,22] suggested that diphenhydramine might partially protect the enzyme from additional inhibition induced by OP or CA insecticides. However, at the current stage, we cautiously draw such a conclusion, since the prediction of a future study by the drapery plot suggested the possibility of a shift of the point of effect size toward the diphenhydramine intervention.…”
Section: Discussionmentioning
confidence: 97%
“…Studies in humans [23,24] and animals [9,25] have demonstrated that diphenhydramine can be used as an alternative, but not a substitute, antidote against poisoning induced by ChE-inhibiting OP or CA insecticides. The antidotal effects of diphenhydramine against poisoning by OP or CA insecticides in experimental animals have been well documented [11][12][13][14][15][16][17][18][19][20][21][22]. Regarding the proposed mechanism behind the antidotal action of diphenhydramine, this has been attributed to its potent antimuscarinic [9][10][11] and possibly antinicotinic effects [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations